SOCIAL ANXIETY SCALE FOR ADOLESCENTS (SAS-A): RELIABILITY TEST - Kurniawan, Vendi Eko; Putra, Kusuma Wijaya Ridi; Sari, Gevi Melliya; Vidhiastutik, Yusiana (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2024)
Background: Adolescents often experience social anxiety caused by acts of body shaming carried out by their friends. This condition causes adolescents to feel that they are not accepted by their surrounding environment. Objectives: This study aimed to analyze the reliability of the Social Anxiety Scale for Adolescents (SAS-A). Design: This research uses descriptive analysis research with a cross-sectional approach. Methods: This research was conducted on May 15, 2023 at Madrasah Aliyah Raden Rahmat, Mojowarno, Jombang. The research instrument used was the Social Anxiety Scale for Adolescents which was adopted from Firdausi (2018) which consists of 18 favorable questions. The research instrument consists of three components, including Fear of Negative Evaluation (FNE), Social Avoidance and Distress with New Social Situation and Unfamiliar Peers (SAD-New), and Social Avoidance and Distance General (SAD-G). Data analysis carried out was Mean, Standard Deviation (SD), and reliability test (Cronbach Alpha) using SPSS 21. Results: Based on the research results, it was found that the Social Anxiety Scale for Adolescents had high reliability test results marked by a Cronbach's Alpha value of .855 (Min = 40.0; Max = 77.0; Mean = 57.94; SD = 10.216). Conclusion: The results of this study indicate that the Social Anxiety Scale for Adolescents is very suitable for use in assessing social anxiety in adolescents at Madrasah Aliyah.